OP40 Efficacy of risankizumab induction and maintenance therapy by baseline Crohn's Disease location: Post hoc analysis of the phase 3 ADVANCE, MOTIVATE, and FORTIFY studies. (21st January 2022) - Bossuyt, P; Bresso, F; Dubinsky, M; Ha, C; Siegel, C; Zambrano, J; Kligys, K; Kalabic, J; Zhang, Y; Panaccione, R
Abstract: Background: In Crohn's disease (CD), disease location affects treatment outcomes. 1 This post hoc analysis assessed the efficacy of risankizumab (RZB), an interleukin 23 p19 inhibitor, by disease location. Methods: In ADVANCE (NCT03105128) and MOTIVATE (NCT03104413), patients with moderately to severely active CD and intolerance or inadequate response to conventional and/or biologic therapy (ADVANCE) or to biologic therapy (MOTIVATE) received intravenous (IV) RZB induction therapy or placebo (PBO) for 12 weeks. Patients achieving clinical response to IV RZB induction were re-randomised in a maintenance study (FORTIFY, NCT03105102) to receive subcutaneous (SC) RZB or SC PBO (ie, withdrawal) for 52 weeks. This post hoc analysis included patients who received RZB 600 mg IV in either ADVANCE or MOTIVATE and patients who received RZB 360 mg SC in FORTIFY. Clinical and endoscopic outcomes were evaluated in patient subgroups stratified by CD location at baseline (ileal only, colonic only, ileal-colonic) using non-responder imputation incorporating multiple imputation to handle missing data due to COVID-19. Results: At week 12, significantly greater proportions of patients receiving RZB 600 mg IV achieved the co-primary endpoints CD Activity Index (CDAI) clinical remission and endoscopic response vs PBO in the colonic only (n = 190) and ileal-colonic (n = 252) subgroups ( P < .001; Figure 1A–1B ). At week 12, statistically higher proportions of RZB-treated patients achieved the composite endpoint CDAI clinical remission and endoscopic response, as well as endoscopic remission in the colonic only and ileal-colonic subgroups vs PBO ( P < .001; Figure 1C–1D ). At week 52, significantly greater proportions of patients receiving RZB 360 mg SC achieved the co-primary endpoints CDAI clinical remission and endoscopic response, composite CDAI clinical remission and endoscopic response, and endoscopic remission vs withdrawal (PBO SC) in the colonic only (n = 59) and ileal-colonic (n = 67) subgroups ( P ≤ .05; Figure 2A–2D ). In patients with endoscopic remission after 12 weeks of IV RZB (week 0 of maintenance), significantly more RZB-treated patients achieved sustained endoscopic remission at week 52 vs withdrawal (PBO SC) in the colonic only and ileal-colonic subgroups ( P ≤ .01; Figure 2E ). At weeks 12 and 52, efficacy rates were numerically lower in ileal only CD relative to colonic only and ileal-colonic CD. Results for ileal only CD are limited by the small number of patients in the subgroup (induction, n = 85; maintenance, n = 15). Conclusion: RZB induction and maintenance therapy was effective in patients with moderately to severely active CD with greater benefits observed in patients with any colonic involvement.